Friedmannia: a new genus from the Seychelles and the beginning of a generic realignment of Curculigo (Hypoxidaceae) - Kocyan, Alexander; Wiland-Szymańska, Justyna (Phytotaxa, 2016)
Recent molecular phylogenetic reconstruction of the monocot Hypoxidaceae implies that the genus Curculigo is non-monophyletic. Curculigo seychellensis occurs on the Seychelles islands and is part of an isolated though geographically well-defined clade. However, Curculigo seychellensis differs in a wide range of character-states from other species of Curculigo and from the genus Hypoxidia, representing the sister clade of C. seychellensis. Therefore, we here propose a new—though monotypic—genus, endemic to the Seychelles: Friedmannia. A detailed reasoning combined with a whole set of new data is presented. A neotype for the genus and the species is designated here.